Enhancing social cooperation through hiking tourism: A case study of the Selo route in Mount Merbabu National Park - Hasan, Muhammad Aqil (Journal of Sustainability, Society, and Eco-Welfare, 2024)
Background: Mount Merbabu is one of the leading natural tourist destinations in Central Java that attracts local and foreign tourists, primarily through the Selo Trail, which is famous for trekking activities. The number of visitors along the Selo Trekking Trail has increased significantly yearly. Tourism activities on this trail have a significant social and economic impact on the surrounding community, directly and indirectly. Therefore, it is essential to identify the social impact and estimate the economic impact of tourism in the area around the Selo Trekking Trail. Method: This research method uses a qualitative descriptive analysis method with a Likert scale to highlight tourism activities' social and economic impacts. This analysis involves collecting data through interviews, questionnaires, and observations to gain in-depth insight into the impact of tourism on local communities and their contribution to their economy. Findings: The study results indicate that tourism activities along the Selo Trekking Trail significantly influence community cooperation and social values. Tourism activities also contribute to community livelihoods, including actively managing tourism and forming volunteer groups. The interaction between tourists and local communities changes culture and social values ​​and has a positive impact by rapidly diversifying residents' jobs. Conclusion: From the results of the study, it can be concluded that tourism on the Selo Trekking Trail has significant social and economic impacts on the surrounding community. This activity strengthens community cooperation, influences social values, and improves livelihoods and job diversification. Active community involvement in tourism management and forming volunteer groups are critical factors in optimally utilizing tourism opportunities. Novelty: This study provides new insights into how tourism on the Selo Trekking Trail affects the social and economic dynamics of local communities. The findings highlight positive changes in community cooperation, social values, and job diversification, which have yet to be widely explored in previous studies on the impact of tourism in the area. This study also underlines the importance of active community involvement in tourism management to maximize economic and social benefits.